2016
DOI: 10.1002/lio2.41
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of peripheral nerve regeneration through biomaterial conduits via micro‐CT imaging

Abstract: ObjectiveHollow nerve conduits made of natural or synthetic biomaterials are used clinically to aid regeneration of peripheral nerves damaged by trauma or disease. To support healing, conduit lumen patency must be maintained until recovery occurs. New methods to study conduit structural integrity would provide an important means to optimize conduits in preclinical studies. We explored a novel combined technique to examine structural integrity of two types of nerve conduits after in vivo healing.Study DesignMic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…35 The association between increased conduit wall thickness and decreased nerve regeneration is likely mediated by decreased nutrient diffusion and wall porosity. 36 In vitro , it has been shown using a material degradation and diffusion study that the optimal conditions for peripheral nerve repair are achieved with a conduit wall thickness of 0.6 mm, a porosity of 80%, and a pore size range of ~10–40 µm. 37 In a rodent model, it has also been shown that biodegradable nerve guides optimally aid nerve regeneration when featuring an internal diameter of 1.5 mm and a wall thickness of 0.3 mm.…”
Section: Methodsmentioning
confidence: 99%
“…35 The association between increased conduit wall thickness and decreased nerve regeneration is likely mediated by decreased nutrient diffusion and wall porosity. 36 In vitro , it has been shown using a material degradation and diffusion study that the optimal conditions for peripheral nerve repair are achieved with a conduit wall thickness of 0.6 mm, a porosity of 80%, and a pore size range of ~10–40 µm. 37 In a rodent model, it has also been shown that biodegradable nerve guides optimally aid nerve regeneration when featuring an internal diameter of 1.5 mm and a wall thickness of 0.3 mm.…”
Section: Methodsmentioning
confidence: 99%
“…This application of hydrogels in skin tissue engineering has been mainly developed because of the drawbacks associated with the use of autografts and allografts where the donor site suffers from pain, recurrent infections, scarring over a while. Tissue-engineered skin replacements have found widespread applications in wound healing, especially in the case of burns, where the major limiting factor is the availability of autologous skin [131,132].…”
Section: Application Of Smart Hydrogels For Tissue Engineeringmentioning
confidence: 99%
“…Also, it has been shown that a PCL conduit can improve motor functional recovery by increase in sciatic functional index (SFI) values, recovery in muscle atrophy, and increase in number of regenerated axons in the sciatic nerve gaps due to creating proper porosity and increase of vascularization in the implanted site (Pixley et al, ; Zhu et al, ). Therefore, this polymer can be considered as one of the most suitable candidates for fabricating the neural conduit.…”
Section: Materials For Fabricating Nerve Conduitsmentioning
confidence: 99%